Machine reliability management system - Boltukov, K. (Запоріжжя : ТДАТУ, 2024)
EN: Quality management of machines is the establishment, provision and maintenance of a given level during design, production and operation, carried out through systematic control and purposeful influence on conditions and factors that affect quality. It is important to replace individual and separate measures with their complex, which ensures a given level of quality at all stages of development, manufacture, operation and repair of machines.
Keywords: management system; agricultural machinery; diagnostics; maintenance are carried